Resistivity thresholds to evaluate durability of concrete with waterproofing agents and different water/cement ratios - Guzmán, Alberto (Revista ALCONPAT, 2023)
In the present work it is evaluated how the variation of the water/cement ratio influences the electrical resistivity of the concrete; the type of cement selected (CPP and CPF); and the incorporation of a water repellent. Cylindrical specimens were made on which the resistivity was evaluated using the Wenner probe method. Comparing the results obtained with the threshold values indicated in the literature, it is possible to understand the importance of this degradation mechanism that implies limiting the maximum w/c ratio to 0.45. On the other hand, the CPP cement turned out to be the one with the best performance, giving rise to higher resistivity results, while the incorporation of the water repellent had a null or counterproductive effect on said parameter. Keywords: durability; corrosion; Wenner probe; electrical resistivity